Decolonizing the Presentation of Research Findings: Amplifying Epistemic Authority Through Poetic Re-Storying - Raymond, Cathy (Narrative Works)

(untitled) (Centre for Digital Scholarship, University of New Brunswick, 2022)
Western-centric epistemologies are often deemed to be more legitimate than non-western ones for driving academic research and knowledge production. As a result, non-western epistemologies are often colonized or silenced during the research process. Decolonizing research practices, such as robust collaboration, mutual respect, mindful listening, and co-constructed interviews offer meaningful opportunities for researchers vested in engaging in research which honors and amplifies a diversity of storied experiences and non-dominant epistemologies. This paper focuses on decolonizing research report writing through poetic re-storying and will include a rationale for and excerpts from a poetic re-storying of research findings from a narrative inquiry project with Parvana, an Afghan woman who until recently was living in Afghanistan; the narrative study is theoretically and conceptually informed by postcolonial feminist theory and the decolonization of research methods. By carefully and collaboratively crafting the research findings in poetic form using original excerpts from open-ended interviews, co-constructed interview conversations, Parvana’s written stories, conversations about artifacts, and other data sources, Parvana and I worked together to amplify and honor her epistemic authority and literacy practices. In addition to presenting the research findings in research participants’ own words, creative re-storying through poetry makes research findings accessible to academic and non-academic audiences alike while also cultivating emotional engagement and empathy.